"Self" Takes it All in Mental Illness: Examining the Dynamic Role of Health Consciousness, Negative Emotions, and Efficacy in Information Seeking. Issue 8 (3rd July 2019) - Lee, Jiyoung
ABSTRACT: Mental illness such as depression, stress, and anxiety disorder is prevalent in our everyday lives. Yet, little is known about how health-related variables operate in the mental illness context. Centering on health consciousness, this study systematically examines how health consciousness affects information seeking and whether negative emotions and efficacy intervene in the relationship in mental illness. The results of the survey ( N  = 614) suggest that health consciousness relates to fear, anxiety, self-efficacy, and response efficacy but does not relate to information seeking. Interestingly, self-efficacy is the only mediator in the relationship between health consciousness and information seeking on mental illness. Implications are discussed.